(untitled) (Jurnal Pendidikan Fisika, 2025)
The increasing complexity of abstract concepts in physics education and the low level of students’ critical thinking skills demand innovative instructional strategies aligned with 21st-century competencies. This study aims to analyze students’ critical thinking skills as the foundation for developing physics interactive multimedia using a generative learning model integrated with a cognitive conflict strategy. The research was conducted in three public high schools in Lima Puluh Kota Regency using a quantitative descriptive survey method, involving 125 eleventh-grade students. Data were collected using five validated instruments: teacher questionnaires on instructional practices and critical thinking, student learning style and attitude surveys, a multimedia needs assessment, and a critical thinking skills test. Results show that current instruction relies heavily on static and non-interactive media such as PowerPoint and videos, failing to support students’ varied learning styles especially the dominant visual preference (53.06%). While students exhibit moderately positive attitudes toward physics learning (65.69%), their critical thinking skills are critically low (average score 27.80%), particularly in inference (24.00%) and evaluation (28.00%) indicators. These findings underscore the urgent need to develop visual and interactive multimedia that facilitates cognitive conflict and deeper reflection. The novelty of this study lies in linking multimedia design with cognitive strategies tailored to enhance critical thinking in physics. The study contributes to physics education by offering empirical evidence for the pedagogical integration of generative learning and cognitive conflict approaches in digital environments, paving the way for targeted multimedia interventions that promote critical reasoning in conceptually demanding physics topics.